Equality or Religious Freedom? The Indiana RFRA. Some Media Representations - Ramona HOSU (Transylvanian Review of Administrative Sciences, 2015)
The paper intends to debate on several media representations of some current social and cultural identities in the USA starting from the controversy that the Indiana Religious Freedom Restoration Act has recently generated. It is to establish the grounding of public opinion regarding the way in which American legislation understands to solve competing constitutional rights while attracting several important actors in the network of disputes over values like equality, freedom, pluralism, justice, democracy. It also comments on individual and community identity construction seen as an ongoing process of ne-gotiation and mobilization of dichotomist beliefs and practices.